2017
DOI: 10.1093/biolre/iox069
|View full text |Cite
|
Sign up to set email alerts
|

Plasma anti-Müllerian hormone profile in heifers from birth through puberty and relationship with puberty onset†

Abstract: The current study aimed to define the plasma profile of anti-Müllerian hormone (AMH) and follicle stimulating hormone (FSH) in heifers during postnatal life until achieving puberty, as defined by plasma progesterone (P4) profile, to demonstrate a relationship between AMH and age of puberty onset. Blood samples collected from 11 Japanese Black female calves within 1 week after birth (W 0) and then biweekly until the sixth week after puberty (WP 6) were assayed for AMH, FSH, and P4. The heifers were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Blood samples pulled at ages of 7, 18, 35, 56 and 86 weeks showed that AMH was highest at 7 weeks and decreased with age. El‐Sheikh et al () and coworkers sampled with greater frequency and found a peak AMH at 10 weeks of age with a decline thereafter. In both studies, AMH reached a stable pattern within the weeks following puberty.…”
Section: Measuring Amh Concentration and Amh Profiles In Cattlementioning
confidence: 99%
“…Blood samples pulled at ages of 7, 18, 35, 56 and 86 weeks showed that AMH was highest at 7 weeks and decreased with age. El‐Sheikh et al () and coworkers sampled with greater frequency and found a peak AMH at 10 weeks of age with a decline thereafter. In both studies, AMH reached a stable pattern within the weeks following puberty.…”
Section: Measuring Amh Concentration and Amh Profiles In Cattlementioning
confidence: 99%
“…Assays were conducted in accordance with the attached instructions. This assay kit can be applied for measuring AMH in cattle as described elsewhere [30].…”
Section: Blood Sampling and Measurement Of Serum Amh Concentrationsmentioning
confidence: 99%
“…The age of onset of puberty in Japanese Black male or female calves is 8 months or 11 months of age, respectively (El‐Sheikh Ali et al., ; Miyamoto et al., ). To compare the plasma levels of AMH in the current case with both female and male calves, blood samples were collected once with no treatment from female Japanese Black calves (pre‐pubertal female group, 6 months old having no corpus luteum, n = 7; post‐pubertal female group, 12 months old having corpus luteum, n = 7), male calves (pre‐pubertal male group, 6 months old, n = 15; post‐pubertal male group, 11 months old, n = 3) and calves at 14 days after castration (castrated group, n = 15).…”
Section: Methodsmentioning
confidence: 99%
“…It is exclusively expressed by granulosa cells in females and Sertoli cells in males. Normally, plasma AMH is higher during the pre-pubertal compared to the post-pubertal period in calves and is higher in males than females reflecting the gonadal capacity for AMH secretion (El-Sheikh Ali et al, 2017;Josso & Picard, 1986;Kitahara et al, 2016;Rota, Ballarin, Vigier, Cozzi, & Rey, 2002). In humans with intersexual disorders, circulating AMH level is a measure of the structural integrity of the gonads; this helps to delineate the cause of the disorder (Lee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%